2018
DOI: 10.3389/fpubh.2018.00359
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Depression, Anxiety, and Mental Representations After Preterm Birth: A Study During the Infant's Hospitalization in a Neonatal Intensive Care Unit

Abstract: Aim: This paper aimed to explore psychological functioning and mental representations in mothers of preterm infants during the child's hospitalization in a Neonatal intensive care unit (NICU).Methods: A sample including 62 mothers of premature infants (gestational age < 37 weeks) was recruited in a NICU. According to the gestational age at the time of delivery, we considered two groups: Group A included mothers whose children were born before 32 weeks of pregnancy; Group B included mothers whose children were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 68 publications
(78 reference statements)
12
101
4
4
Order By: Relevance
“…An unwanted pregnancy may signi cantly change life, be a stressful experience with different impacts on quality of life and may trigger certain psychological problems as anxiety 51 . In our study, the delivery of premature baby is associated with PPA which concluded the same in other studies 52,53 . The underlying reasons for this relation can be depicted by the isolation that the parents are exposed to after the delivery of premature babies that mandate hospitalization due to the di culty in discharging premature infants without being admitted to neonatal intensive care units.…”
Section: Factors Associated With Anxietysupporting
confidence: 91%
“…An unwanted pregnancy may signi cantly change life, be a stressful experience with different impacts on quality of life and may trigger certain psychological problems as anxiety 51 . In our study, the delivery of premature baby is associated with PPA which concluded the same in other studies 52,53 . The underlying reasons for this relation can be depicted by the isolation that the parents are exposed to after the delivery of premature babies that mandate hospitalization due to the di culty in discharging premature infants without being admitted to neonatal intensive care units.…”
Section: Factors Associated With Anxietysupporting
confidence: 91%
“…The mean total healthcare costs were lower in both the matched infants of mothers with PPD and infants of mothers without PPD cohorts after excluding preterm deliveries. Infants of mothers with PPD had higher total healthcare costs than those without PPD, but the difference was no longer significant after excluding preterm deliveries ($18,103 vs. $16,327, p ¼ .077), suggesting preterm birth is a driver of allcause healthcare costs and supporting the previously identified relationship between preterm delivery and risk of PPD [42][43][44] . It is also possible that comorbid conditions in the preterm infant leading to increased HRU and costs could be a contributing factor to the mother's depressive symptoms, instead of the mother's mental health contributing to the infant's health.…”
Section: Discussionsupporting
confidence: 53%
“…The Parent Domain may indicate sources of stress / dysfunction of the parent and child system, whose parents should be referred for evaluation and professional follow-up if levels above the 90th percentile are detected. 9 Data was analyzed according to the guidelines of the Parental Stress Index scale, with Likert-type responses and a range from one to five, corresponding to: totally agree (5); I agree (4); not sure (3); strongly disagree (2) and strongly disagree (1). The result is obtained, firstly, in absolute number or gross score, being transformed into percentile by means of the normative sample table, in which stress scores are classified as: normal stress when the percentiles are between 16 and 84; high stress to the 85th and 89th percentiles and a score equal to or above the 90th percentile, which represents a clinically significant stress level.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, parents need to suddenly adapt to the condition of parents of a premature newborn, and this new condition puts them in an immediate experience of suffering, helplessness, sadness, loneliness, pain, and unpredictability of the clinical situation of the newborn child. 1 The hospitalization of premature newborns, due to their vulnerability, promotes the separation of parents and children, interfering in the formation of attachment and causing emotional distancing between the parties. [2][3] It can be shown the adaptation and reactions of mothers and fathers regarding the hospitalization of premature infants in the Neonatal Intensive Care Unit (NICU), since, since the hospitalization, different feelings related to prematurity, financial and social issues emerge among others by mothers and fathers.…”
mentioning
confidence: 99%